Transport of heterometric sediments in wave-dominated flows – Tracer experiments - Ferreira, Caroline C.; Silva, Paulo A.; Bernabeu, Ana M.; Abreu, Tiago (Marine geology, 2023)
Sediment dynamics is a complex subject, playing an important role in coastal areas. The interaction between wave action and sediment particles is determinant to understand sediment transport processes. The knowledge of sediment transport comprising sand mixtures is relevant as coastal areas, usually, present heterogeneities of sediment particle sizes in the horizontal and vertical directions, denoting the existence of selective transport processes. This study investigates the effects of non-cohesive size-graded sands on sediment transport fluxes to understand selective transport mechanisms under wave-dominated conditions. A laboratory experiment was carried out at the large wave flume (Großer Wellenkanal, GWK) in Hannover, considering distinct sediment mixtures between two well-sorted sands with median grain sizes of 0.21 mm and 0.58 mm. The experiments were carried out for four sediment bed configurations with two different wave energy conditions. A fluorescent sand tracer technique was implemented to measure total and fractional net sediment transport rates and the outcomes are compared with the ones obtained with the mass conservation method. The experimental results show the occurrence of the interaction between different sand fractions: a decrease in the transport of fine sediments and an enhancement of the transport of the coarse sediments as the percentage of coarse sediments in the bed mixture increases. These effects are larger as the coarser fraction in the sand bed increases and they are noticeable for different sediment transport regimes (sheet flow and rippled beds). •Laboratory experiments were carried with sediment mixtures of fluorescent tracer.•The effects of size-graded sand on sediment transport fluxes were studied.•Interaction between distinct fractions modified transport rates of each fraction.